Digital-Droplet PCR for Quantification of CD19-Directed CAR T-Cells - Mika, Thomas; Maghnouj, Abdelouahid; Klein-Scory, Susanne; Ladigan-Badura, Swetlana; Baraniskin, Alexander; Thomson, Julia; Hasenkamp, Justin; Hahn, Stephan A.; Wulf, Gerald; Schroers, Roland (Frontiers in Molecular Biosciences, 2020)
CD19-directed CAR-T-cells (CD19-CAR) have demonstrated remarkable clinical results in patients suffering from refractory or relapsed lymphoma and acute lymphoblastic leukemia. In order to further optimize follow-up, to explain treatment failure, and to control adverse events biomarkers for monitoring of response are urgently needed. Peak expansion and persistence are correlated with response rates and severity of side effects. However, no standardized method or commercially assay for CD19-CAR measurement is established yet. In this study, two primer-probe assays for digital-droplet PCR (ddPCR) were designed and subsequently explored on 54 samples collected from 7 patients after CD19-CAR treatment with axi-cel over time. Detection and quantification of CAR-T-cells were feasible and reliable for all patients included. Peak expansion measured with our assay significantly correlated with the grade of neurologic adverse events (ICANS) but not with cytokine release syndrome. All patients with loss of CAR-signal eventually had disease progression. In summary, our novel assay allows monitoring of CAR-T-cells in vivo and may result in improved safety and efficacy of CAR-T treatment.